Business Strategy Development Using BMC and SWOT to Optimize Tourism Destination Revenue - Putri Regina Yuni Kurniasari; Rosy Aprieza Puspita Zandra; Zainal Abdul Haris (Harmoni Economics: International Journal of Economics and Accounting, 2025)
This study aims to apply the Business Model Canvas (BMC) and SWOT analysis to help optimize revenue, case study at Plaza Bukit Surga, Nganjuk, Indonesia. The method used in this study is a qualitative descriptive approach with data triangulation techniques, including interviews, observations, and documentation. The type of data used is secondary data, comprising visitor data from 2022-2024 and revenue data for the periods of July-December 2023 and 2024. The results of the study indicate that the number of visitors in 2024 decreased by 30% compared to 2022 and 2023, which also affected the decline in revenue. Through the analysis of the nine BMC business elements and the integration of SWOT analysis, it was found that the main weaknesses lie in marketing strategy and resource utilization. This study provides strategic recommendations such as enhancing promotions, strengthening customer relationships, and developing facilities. The analysis shows that BMC is an effective tool for systematically understanding and developing tourism destination business models, and provides a basis for management to develop strategies that adapt to market dynamics. With the right strategy implementation, Plaza Bukit Surga has the potential to become a leading destination contributing to the local economy.